Model Teacher Centric Branding sebagai Strategi Membangun Reputasi Sekolah Islam Terpadu: Studi Kualitatif Deskriptif di Indonesia - Ramadhan, Angga; Karim, Hamdi Abdul (YASIN, 2025)
Although educational branding has received attention in previous studies, research that specifically examines Teacher Centric Branding (TCB) as a teacher-based value approach to building the reputation of Sekolah Islam Terpadu (SIT) remains very limited. This study aims to conduct an in-depth analysis of the mechanisms through which institutional reputation is formed via the internalization of Islamic values, exemplary practice, and the support of teachers’ spiritual leadership as a living brand. The study employs a qualitative approach with an interpretative phenomenological design, involving 12 participants selected through purposive and snowball sampling. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using Interpretative Phenomenological Analysis (IPA). The findings show that value internalization through structured spiritual development serves as the foundation of teachers’ professional identity; teacher role modeling in interactions with students and parents emerges as the most influential factor in shaping public perceptions; and spiritual leadership plays a crucial role in ensuring value consistency and institutional cultural stability. These findings expand theoretical understanding of internal branding, the human brand, and value-based leadership in the context of Islamic education, and affirm that SIT reputation is more strongly built through the quality of teachers’ values and behaviors than through external promotional strategies. The implications of this study include strengthening teacher development programs, enhancing communication competencies, and developing indicators of role modeling as an integral part of school branding strategies, while also opening opportunities for further research in other SIT contexts by involving more stakeholders and employing longitudinal designs to more comprehensively understand the dynamics of TCB formation.